Sujeição e agência em situações de violência contra as mulheres: trajetórias de superação e ressignificação - Érika Nunes de Medeiros Ferreira Borges; Eliane Gonçalves (Ciências Sociais Unisinos)
In this paper we analyze some aspects related to the problem of violence against women from a qualitative research completed recently (2016) with women living in Goiânia, Goiás, who have gone through contexts of violence triggered by their partners – boyfriends or husbands. We explore the meanings attributed to the experiences, attentive to the subjective processes that signal a break and a reframing of the situation of violence suffered by the women, the research subjects. The study focuses on specific characteristics and similarities in the analyzed trajectories and allows to conclude that: (i) despite the relative delay in understanding the context of violence in its early signs, (ii) assigning idiosyncratic traits to partners such as explosive behavior or jealousy and (iii) the reluctance and hesitation to seek help at moment of violence, this group of women managed to give a new meaning to their lives, indicating a desire to overcome what they went through, something already or very close to the outcome in the narratives of them all. Their overcoming points to a shift in power relations, as stressed by feminist studies dealing with the issue of violence. The notion of subjectivity as agency and not only as a subjection leads to the possibility, at least in some contexts, of resistance and freedom of action. It is about this dyad, subjection/agency related to the issue of violence against women, this article aims to deal with.